2011
DOI: 10.1007/s11745-011-3581-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Composition of Triacylglycerols in the Fat Bodies of Bumblebee Males During Their Lifetime

Abstract: The age-dependent changes in the composition of triacylglycerols (TAG) in the fat bodies of bumblebee males were studied using HPLC/MS. Two related species (Bombus terrestris and B. lucorum) were compared, with the age of the males being 0-30 days. The total amount of TAG in B. lucorum was about 2.7 times higher than that in B. terrestris for all of the ages studied. One to three-day-old males had the highest content of TAG in their fat bodies (1.6-2.3 mg/individual in B. terrestris and 3.8-4.2 mg/individual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Jiroš et al. found that bumblebee males hatch with fully developed FBs,36 which could serve as a source of FAs.…”
Section: Resultsmentioning
confidence: 99%
“…Jiroš et al. found that bumblebee males hatch with fully developed FBs,36 which could serve as a source of FAs.…”
Section: Resultsmentioning
confidence: 99%
“…Beenakkers et al [ 35 ] reported on the existence of two different acylglycerol pools in FB with expected differences in the manner of their utilization. Metabolic TG belonging to group A ( Fig 4 ) dominate also in the males' FB [ 15 ] while queen-specific TG change during the queens' life. This may indicate their relationship to overwintering and possibly also to future egg formation and/or development with their special metabolic requirements beyond the needs of short-lived males.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC/MS with atmospheric pressure chemical ionization (APCI) was used for the TG analyses as described by Jiroš et al [ 15 ]. In order to evaluate the total lipid composition, we used HPLC combined with electrospray ionization mass-spectrometry (MS-ESI) (modified according to ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Established protocols for year‐round breeding of Bombus terrestris provides a continuous source of specimens of defined ages and physiological condition. This allows for the investigation of temporal changes in MP composition, along with other aspects of Bombus terrestris physiology and behaviour (Šobotník et al ., ; Žáček et al ., ; Jiroš et al ., ; Jarau et al ., ; Brabcová et al ., ; Buček et al ., ; Prchalová et al ., ).…”
Section: Introductionmentioning
confidence: 99%